Kritik Sosial dalam Cerpen “Dari Masa Ke Masa” Karya A.A. Navis: Tinjauan Sosiologi - Agust Furi Kartika Panjaitan (JURNAL ILMIAH NUSANTARA, 2026)
Literature serves as a medium for reflection and social criticism of societal realities. Based on this function, this study examines social criticism in the short story "Dari Masa Ke Masa" by A.A. Navis using a sociology of literature approach. This study uses a descriptive qualitative method with text analysis techniques on quotations that represent the characters' social attitudes and behaviors. The results show that the relationship between the older and younger generations is depicted unequally through authoritarian, opportunistic attitudes, monopoly of knowledge, claims to achievement, and intergenerational skepticism, which are reinforced by informal control behavior, organizational co-optation, internal conflict, group disintegration, and symbolic submission. These findings confirm a paternalistic relationship pattern that positions youth as objects of legitimacy and reproduces intergenerational power structures.